A new ESIPT-based fluorescent probe for highly selective and sensitive detection of hydrogen sulfide and its application in live-cell imaging. (9th January 2017) - Chen, Bo; Huang, Jing; Geng, Huiqing; Xuan, Lingli; Xu, Tengfei; Li, Xin; Han, Yifeng
Abstract : A new ESIPT-based fluorescent probe for the sensitive detection of hydrogen sulfide has been reasonably designed and developed. Abstract : A new excited-state intramolecular proton transfer (ESIPT) based fluorescent probe for the detection of hydrogen sulfide has been reasonably designed and developed. The probe operates by H2 S-mediated reduction of hydroxylamine to amine and exhibits high selectivity and sensitivity under mild conditions. Furthermore, the probe was successfully used for fluorescence imaging of H2 S in living cells.